Edukasi Budidaya Edamame Organik di Kelurahan Cempaka, Kota Banjarbaru dalam Mendukung Sistem Pertanian Berkelanjutan: Education on Organic Edamame Cultivation in Cempaka Village, Banjarbaru City in Encouraging Sustainable Agriculture Systems - Akhmad Gazali; Rabiatul Wahdah; Akhmad Rizali; Hairu Suparto; Jumar Jumar; Untung Santoso; Riza Adrianoor Saputra; Noorkomala Sari; Muhammad Imam Nugraha; Munanto Munanto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Edamame, as an essential food ingredient, has the potential to be developed with a high level of market demand every year. The ability of edamame cultivated on all types of soil has the opportunity to be introduced to the residents of Cempaka Village, Banjarbaru. The introduction of integrated pest control-based cultivation and land management using compost media from agricultural waste by considering environmental sustainability needs to be conveyed and later applied to build environmentally friendly sustainable agrarian concepts. The purpose of this Community Service Activity is to educate and train the skills of the people of Cempaka Village, Banjarbaru City, regarding organic edamame cultivation to improve the quality of edamame cultivation and production sustainably. The method used in this activity is a classical approach in the form of lectures and distributing knowledge questionnaires before and after the extension material. The results of the pre-activity questionnaire showed that 65% of participants only knew about edamame, compost, and organic fertilizers but not about integrated pest control techniques. After the activity, participants' knowledge increased by approximately 100%, hoping that the Cempaka Village community could apply it in the field.